FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Primaditha, Luh Priyanka Padma; Harahap, Harrie Supriatna (Jurnal Akuntansi dan Keuangan, 2019)
The objective of this study is to obtain empirical evidence about the influence of managerial ownership, independent board of commissioner, audit committee, firm size, profitability, sales growth, firm age, dividend policy, board size, and debt policy to value of corporate that listed in Indonesian Stock Exchange for the period from 2015-2017. The analysis purposive sampling method in the sample selection. There is 55 companies that selected to be final sample. The findings of this study shows that independence board of commissioner, profitability, sales growth, and debt policy affected corporate value. On the other hand, managerial ownership, audit committee, firm size, firm age, dividend policy, and board size did not affect corporate value